Supplementary Cementitious Materials in Concrete - Fantilli, Alessandro P.; Jóźwiak-Niedźwiedzka, Daria (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
The articles featured in this Special Issue cover different aspects of the design, testing, and application of various types of supplementary cementitious materials in concrete. The results of the research, conducted by over 50 international universities and scientific centers, prove the great interest in the SCM topic.